THE INFLUENCE OF PRODUCT QUALITY, BRAND IMAGE AND PRICE ON THE DECISION TO PURCHASE TOTO SANITARYWARE PRODUCTS AT PT. SINAR GLASSINDO JAYA - Chandra, Jennifer; Chua, Johannes (Procuratio : Jurnal Ilmiah Manajemen, 2025)
This research aims to determine and analyze the influence of product quality, brand image and price on purchasing decisions for sanitaryware products at PT. Sinar Glassindo Jaya. The population in this study consisted of all customers who purchased TOTO sanitaryware at PT. Sinar Glassindo Jaya in Pekanbaru City is known. Determining the sample in this study used accidental sampling. The number of samples obtained was 140 respondents. The analytical method for this research uses descriptive analysis and several types of evaluation using the IBM SPSS (Statistical Software for Social Science) program. So the research results show that product quality, brand image and price have a positive and significant effect on purchasing decisions for sanitaryware products TOTO at PT. Sinar Glassindo Jaya. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh kualitas produk, citra merek dan harga terhadap keputusan pembelian produk sanitaryware di PT. Sinar Glassindo Jaya. Populasi dalam penelitian ini terdiri dari seluruh pelanggan yang melakukan pembelian sanitaryware TOTO di PT. Sinar Glassindo Jaya di Kota Pekanbaru yang diketahui. Penentuan sampel dalam penelitian ini menggunakan accidental sampling. Jumlah sampel yang diperoleh sebanyak 140 responden. Metode analisis penelitian ini menggunakan analisis deskriptif serta beberapa jenis evaluasi dengan menggunakan bantuan program IBM SPSS (Software Statistical for Social Science). Maka Hasil Penelitian menunjukkan bahwa kualitas produk, citra merek dan harga berpengaruh positif dan signifikan terhadap keputusan pembelian produk sanitaryware TOTO di PT. Sinar Glassindo Jaya.